The auxin transport inhibitor 2,3,5-triiodobenzoic acid (TIBA) inhibits the stimulation of in vitro lateral root formation and the colonization of the tap-root cortex of Norway spruce (Picea abies) seedlings by the ectomycorrhizal fungus Laccaria bicolor - Karabaghli-Degron, C (The New phytologist, 1998)
Norway spruce (Picea abies (L.) Karst.) seedlings were inoculated with the ectomycorrhizal fungus Laccaria bicolor ((Marie) Orton), strain S238 N, in axenic conditions. The presence of the fungus slowed tap-root elongation by 26% during the first 15 d after inoculation and then stimulated it by 136%. In addition, it multiplied in vitro lateral root formation by 4.3, the epicotyl growth of the seedlings by 8.4 and the number of needles by 2. These effects were maintained when the fungus was separated from the roots by a cellophane membrane preventing symbiosis establishment, thus suggesting that the fungus acted by non-nutritional effects. We tested the hypothesis that IAA produced by L. bicolor S238 N would be responsible for the stimulation of fungal induced rhizogenesis. We showed in previous work that L. bicolor S238 N can synthesize IAA in pure culture. Exogenous IAA supplies (100 and 500 μm) reproduced the stimulating effect of the fungus on root branching but inhibited root elongation. The presence of 2,3,5-triiodobenzoic acid (TIBA) in the culture medium significantly depressed lateral root formation of inoculated seedlings. As TIBA had no significant effect on IAA released in the medium by L. bicolor S238 N, but counteracted the stimulation of lateral rhizogenesis induced by an exogenous supply of IAA, we suggest that TIBA inhibited the transport of fungal IAA in the root. Furthermore TIBA blocked the colonization of the main root cortex by L. bicolor S238 N and the formation of the Hartig net. These results specified the role of fungal IAA in the stimulation of lateral rhizogenesis and in ectomycorrhizal symbiosis establishment